Edukasi Pemanfaataan Gelatin Organik Sehat dan Ramah Lingkungan dari Tulang Patin di Kampung Patin Kabupaten Kampar - Rahimatul Uthia; Ira Oktaviani RZ; Yeni Aryani (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
It's known that gelatin is a protein made from the skin and bones of animals, such as cows or pigs. The protein is a derivative of collagen type of protein found in skin, bones, and muscles. Meanwhile, the source of gelatin obtained from Patin bones, where Riau Province is one of Patin development center in Indonesia, make this easy to obtain Patin bones as a source of gelatin. Besides Patin, Kampar Regency also has the potential pineapple commodities. Pineapple production centers in Kampar Regency located in Tambang District, namely in Kualu 2 Nenas Village and Rimbo Panjang Village with an average production of 875 tons/hectare and 1.6 tons/hectare, respectively. This is what underlies the use of pineapple peel as a gelatin extractor from Patin's bones so that the gelatin obtained later is an organic gelatin extract that is healthy and environmentally friendly. Therefore, it is deemed necessary for a Patin processing center to know other benefits of Patin bones that make organic gelatin.